Determination of estradiol metabolites in human liver microsome by high performance liquid chromatography-electrochemistry detector - Cheng Ze-Neng; Huang Song-Lin; Tan Zhi-Rong; Wang Wei; Zhou Hong-Hao (Acta Pharmacologica Sinica, 2016)
Aim: To constitute a method to determine the estradiol metabolites in human liver microsome in low concentration of estradiol. Methods: Use high performance liquid chromatography after solvent extraction, evaporation, and reconstitution to separate the metabolites and use a electrochemistry detector to detect the metabolites. Results: With a mobile phase of acetic acid buffer-acetonitrile (50:50, v/v, pH 4.5) at flow rate of 1.0 mL/min and a potential of +0.7 V vs Ag/AgCl, all six composition were well separated and satisfactorily detected. There are E3, 16alpha-OHE1, 2-OHE2, E1, and two unidentified composition. The minimum detectable amount is about 100 p g on column. This method is sensitive enough to detect E1 in a substrate concentration of 1 micromol/L. Conclusion: The method can be used to study the metabolism mechanism of estradiol in liver microsome.